(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current status of nursing care for lung cancer patients at Nghe An Oncology Hospital and analyze related factors. Materials and methods: This study aimed to evaluate the current status of nursing care for 176 lung cancer patients at Nghe An Oncology Hospital from March to September 2024 and identify related factors, using a cross-sectional descriptive design. Results: The results showed that the quality of nursing care was rated favorably by patients, with the rate of good ratings increasing from 66.5% (at admission) to 77.3% (at discharge). Aspects of care such as reception (79.5%), nutritional care (77.3%), personal hygiene care (80.1%), psychological counseling (80.7%), treatment monitoring (88.1%), and implementation of medical orders (80.7%) were all highly rated. The study also revealed that female patients were 2.27 times more likely to rate nursing care as poor compared to male patients, and patients in stages I and II were 2.51 times more likely to rate nursing care as poor compared to patients in stages III and IV. Factors such as age, residence, comorbidities, and tumor location were not significantly associated with patient evaluations. Conclusion: Nursing care for lung cancer patients at Nghe An Oncology Hospital was highly rated, particularly in fundamental and specialized care aspects. However, there is a need for focused efforts to improve the quality of care for female patients and those in the early stages of the disease.